Provision of academic data for research: a step for academic success - Miguel, Hugo Gonzaga Parente (2019)
One of the most widely researched questions about higher education focuses on exposing paths that lead to academic success. This dissertation provides a tool aligned with the scientific contributions to the concept of success in higher education, as well as the implementation of a system capable of automatic generation of SQL queries based on high level constraints. It includes the use of students' data contained in the ISCTE-IUL University Fénix system in a web application, to assist analyzes and researches. Providing relevant data for consultation can offer a differentiated explanation of the pathways of success in higher education and identify problems and failures to support more effective intervention measures later.